2015
DOI: 10.7554/elife.04378
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between population firing stability and single neuron dynamics in hippocampal networks

Abstract: Neuronal circuits' ability to maintain the delicate balance between stability and flexibility in changing environments is critical for normal neuronal functioning. However, to what extent individual neurons and neuronal populations maintain internal firing properties remains largely unknown. In this study, we show that distributions of spontaneous population firing rates and synchrony are subject to accurate homeostatic control following increase of synaptic inhibition in cultured hippocampal networks. Reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
139
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(164 citation statements)
references
References 48 publications
(67 reference statements)
19
139
1
Order By: Relevance
“…S1). Moreover, a GABA B R agonist, baclofen, triggered a pronounced block of firing rate that was precisely restored to the baseline level after a period of 2 d (9). The observed compensatory responses to increase in spiking activity by GABA A R antagonist or decrease in spiking activity by GABA B R agonist confirm the idea that homeostatic mechanisms maintain stable circuit function by keeping neuronal firing rate around a "set point" (10,18).…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…S1). Moreover, a GABA B R agonist, baclofen, triggered a pronounced block of firing rate that was precisely restored to the baseline level after a period of 2 d (9). The observed compensatory responses to increase in spiking activity by GABA A R antagonist or decrease in spiking activity by GABA B R agonist confirm the idea that homeostatic mechanisms maintain stable circuit function by keeping neuronal firing rate around a "set point" (10,18).…”
Section: Resultssupporting
confidence: 53%
“…Given a pronounced effect of TTX 48h on spike-evoked synaptic vesicle exocytosis, these results suggest complete blockade of spikes does not trigger compensatory changes in spontaneous vesicle release. In previous studies, mEPSC frequency was found to be immune to chronic TTX treatment in some cases (18,41), while being up-regulated by AMPA receptor blockade (36,41), either by suppression of neuronal excitability (38) or by increase in the GABA B R-mediated inhibition (9). Thus, the induction of presynaptic homeostatic changes may require minimal spiking activity (41).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The question is raised of whether cells have their own set points or whether the circuit as a whole maintains a set point to which each individual neuron contributes, but from a different set point at any given time. Slomowitz et al [14] originally found evidence that individual cells increased or decreased their firing rate to different values but the ensemble average was maintained at a set point [14]. In contrast, Hengen et al [15] recently showed that cells in visual cortex return to within 15% of their own set points following perturbation even though they start from widely differing initial firing rates.…”
Section: The Three Position Papersmentioning
confidence: 99%